Career Fantasies of the Alpha Generation: The Influence of Digital Technology and Parental Guidance in Shaping Future Career Aspirations - Fifin Dwi Pratiwi; Agus Basuki; Edi Purwanta; Elya Rukhana (Universitas PGRI Yogyakarta, 2026)
Every individual has future career aspirations but often faces challenges in realising them. Early career awareness and planning through career exploration is an important factor in their achievement. In elementary school-aged children, this exploration is still at the fantasy stage, where they are interested in professions that they often see. This study examines the career fantasies of Generation Alpha and the factors that influence them. Using a descriptive quantitative approach, this study involved 100 students in grades 3-6 in a remote school in Lampung, selected through purposive sampling. Data were collected through an open-ended questionnaire related to professional interests, reasons for choosing a profession, and sources of information that influence career fantasies. The results showed that doctors, teachers, police, and soldiers were the most frequently chosen professions by students. Gender, family, school, and digital media influence career fantasies. The findings have implications for career education and guidance, supporting children's early career development. Keywords: career fantasies, alpha generation, digital technology, career development